2005
DOI: 10.1097/01.hjh.0000163159.22116.ab
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antihypertensive effects of an angiotensin-converting enzyme inhibitor, a calcium antagonist and a diuretic in patients with hypertension not controlled by angiotensin receptor blocker monotherapy

Abstract: In patients in whom hypertension was not controlled by full-dose ARB monotherapy, a diuretic, a calcium antagonist or an ACE inhibitor provided significant additional antihypertensive effect. The antihypertensive effects of the ARB-diuretic and the ARB-calcium antagonist combinations were superior to that of the ARB-ACE inhibitor combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 37 publications
(65 reference statements)
1
27
0
1
Order By: Relevance
“…In hypertensive patients whose BP could not be controlled by the maximum dose of an Rationale, design and implementation of COLM study T Ogihara et al ARB, adding a diuretic or CCB was reported to enhance the antihypertensive effect. 17,18 The ultimate goal of combination therapy is to reduce cardiovascular outcomes in addition to reducing BP. Only two large-scale randomized clinical trials have investigated which combination of antihypertensive agents is more effective in preventing cardiovascular diseases in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In hypertensive patients whose BP could not be controlled by the maximum dose of an Rationale, design and implementation of COLM study T Ogihara et al ARB, adding a diuretic or CCB was reported to enhance the antihypertensive effect. 17,18 The ultimate goal of combination therapy is to reduce cardiovascular outcomes in addition to reducing BP. Only two large-scale randomized clinical trials have investigated which combination of antihypertensive agents is more effective in preventing cardiovascular diseases in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Обе комбинации продемонстрировали высокую эффективность, особенно в отдельных клинических группах паци-ентов. Необходимо отметить, что некоторые ком-бинации более эффективны, чем другие, как пока-зали Stergiou et al [28]. Так, комбинация препара-тов, действующих на одни и те же патогенетические механизмы, может быть менее эффективна, чем сочетание препаратов с разными механизмами дей-ствия.…”
Section: следующий шаг: фиксированная комбинацияunclassified
“…Combining classes of agents with complementary mechanisms of action, such as CCBs and RAS blockers, provides greater BP-lowering efficacy than monotherapy, [68][69][70][71][72][73][74][75] with a comparable and potentially improved adverse-event profile. 76 However, few trials have been designed to test the effect of specific antihypertensive combinations on cardiovascular or renal end points.…”
Section: Dual Calcium Channel/ras Blockadementioning
confidence: 99%